E-Module Assisted by Augmented Reality with a Discovery Learning Model on Virus Material to Increase Scientific Literacy and Learning Independence for Class X High School Students - Retno Sandi Saputra; Bernadetta Octavia (Postgraduate, University of Mataram, 2024)
This study aimed to assess the feasibility, practicality, and effectiveness of an e-module assisted by augmented reality with a discovery learning model on virus material to increase scientific literacy and learning independence for class X high school students. The study employed the ADDIE development model by Dick and Carey, employing a quasi-experimental, nonequivalent pretest-posttest control group design. The study involved 60 grade X students from SMA Negeri 1 Pengasih, with class X1 as the control group and X2 as the experimental group selected through cluster random sampling. Various instruments were utilized, including questionnaires from media and material experts, assessments by biology teachers, student responses, as well as tests on learning independence and science literacy. Data analysis encompassed descriptive and inferential statistics. The findings indicated the e-module's suitability, with media experts rating it at 98.37% and material experts at 99%. The practicality evaluation by biology teachers yielded a score of 95.32%, while student responses reached 96.96%. The N-Gain test demonstrated a substantial increase, and the One-Way MANOVA test indicated statistical significance (p <0.05). This e-module has demonstrated its viability, practicality, and efficacy in enhancing scientific literacy and learning independence concerning virus material.